Safety assessment in construction projects based on the effectiveness of the project knowledge management maturity model - Javad Hasanali; Faezeh Taherkhani; Shadi Motamedi (مهندسی و مدیریت ساخت, 2020)
Today, according to the rapid development in construction industry in our country, safety issues in construction sites become a serious challenge. So, paying attention to the safety, indicating effective factors and safety evaluation in projects are essential in order to improving construction projects safety. This paper is conducted to assess the effectiveness of project management maturity model on safety standards in mass construction projects. A Researcher made questionnaire with approved reliability and validity was used in this paper and based on this questionnaire the effectiveness of project management knowledge maturity model on important safety indicators of projects such as performance, cost, time and safety quality has been evaluated. The mentioned questionnaires were distributed between mass production projects in District 1 in Tehran province and collected data were analyzed by SPSS software and regression techniques. The results of regression analysis indicate the strong and positive effects of the project management knowledge maturity model on the standard safety of projects. Therefore, it can be concluded that the application of project management knowledge maturity model in mass production projects has a significant impact on improving the standard safety indicators of projects and in addition to increasing safety performance, safety costs and the waste of time reduction will greatly increase the safety quality of projects.